(3EJMGa GdfhGXQ HeNJUQ GdRhGLQs - (3GdCMSGFj GdMfaj, GdedG, CHh HcQ Hf eMeO Hf YeQ, J(B1270(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj hab ef TGACeG HYO aEf cJGH GdRhGLQ Yf GbJQGa GdcHGFQ GdPj Cdag GdEeGeGHf MLQ GdgjKej cJGH LdjdhdeG QCjJ HYV GdeTJZdjf HGdbQGAI ajgCMHHJ Cf CdNUghSejJg EJMGa GdfhGXQs
(3BNQgG (B:s
{(3hfhOhG Cf Jdce GdLfI GdJj ChQKJehgG HeG cfJe JYedhf(B} (3LYdfG Gddg ef Cgd GdLfI GdPjf CMd Ydjge QVhGfg hCOGe dge LhOg hcQeg hEMSGfg hCefG aj GdOGQjf Yf SGFQ GdaJf hGdeMf Efg Ydi cd TjA bOjQ hHGdELGHI NHjQs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B1236(3g` , hebGHdI heUMMI (B1280(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2/ 70s
(3eYLe GdeDdajf(B: 1 / 446s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs